2018
DOI: 10.1049/iet-map.2017.1029
|View full text |Cite
|
Sign up to set email alerts
|

Study of rain attenuation effects for 5G Mm‐wave cellular communication in tropical location

Abstract: Millimetre (mm)‐wave communication is a viable solution to the future 5G cellular services. For different temperate locations, rain attenuation does not contribute significantly to the overall path loss at the mm‐wave band for a small cell size of 200 m. However, in various tropical locations, the rain attenuation effect cannot be ignored even for this small cell size of the system. If the authors increase either frequency or path length, the attenuation increases significantly under tropical raining condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 9 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…The atmospheric oxygen absorption is especially severe at 60 GHz and 120 GHz, and the water vapor absorption is particularly very high at 180 GHz [31]. Also, rain attenuation at mmWave frequencies is much greater than that of sub-6 GHz frequencies [32].…”
Section: A Propagation Characteristicsmentioning
confidence: 98%
“…The atmospheric oxygen absorption is especially severe at 60 GHz and 120 GHz, and the water vapor absorption is particularly very high at 180 GHz [31]. Also, rain attenuation at mmWave frequencies is much greater than that of sub-6 GHz frequencies [32].…”
Section: A Propagation Characteristicsmentioning
confidence: 98%
“…Tropical location received more rain due to heavy rainfall and caused rain attenuation. Therefore, paper in [71] conducted simulation on to test the channel model for rain attenuation in tropical location specifically in Kalkota and Spina d'Adda for 28 GHz and 28 GHz frequencies by using time series of rain rate prediction as shown in [72]. Method in [72] separated all rain rate data into three segments; constant (C), down (D) and up (U).…”
Section: Rainmentioning
confidence: 99%
“…Besides, mmWave provides highcapacity and line-of-sight (LoS) dominated connectivity for UAVs, it also suffers from many challenges, such as rapid channel variation, blockage effects, atmospheric attenuations, range limits etc. [8], [9], leading to substantial interference problems especially in multi-cell scenarios. The recent studies have even reported nearly 150 UAV crashes occurred due to loss of communication with ground base stations [10].…”
Section: Introductionmentioning
confidence: 99%